ANALISIS DESAIN SUMUR RESAPAN PADA KAWASAN PEMUKIMAN DI BANJARBARU - Irfan Prasetia (Universitas Lambung Mangkurat, 2014)
Growth in residential area in Banjarbaru, South Borneo, Indonesia, is significantly reduce the water catchments area. This leads to surface runoff occurs during the monsoon season which ultimately has the potential to cause flooding. One of the effective solutions to solve this problem is by making infiltration well in the residential area. This research was conducted to analyze the design of the infiltration well in the residential area, especially in Banjarbaru. To facilitate the research works, the residential area of Lambung Mangkurat University’s lecturer in Banjarbaru, South Borneo was chosen. As for the hydrology and soil Data of the research works area was taken from the community service report of the lecturer team of the Faculty of Engineering Unlam Banjarbaru. The results shows that the ideal dimension for the infiltration well in Banjarbaru is by using the radius of the well (R) of 1.25 m. With the R of 1.25 will give a significant recharge to the groundwater. This R will give the equal recharge to the groundwater for infiltration wells with a flat bottom and lower soil layer porous and upper soil layer impermeable, infiltration wells with impermeable wall, and infiltration wells with porous wall. Keywords: Infiltration well, radius of infiltration well, groundwater reservation